Reducing Parental Perceived Barriers to HPV Vaccine Uptake Through a Community-Based Nurse-Led Educational Intervention in Kaduna North Senatorial District, Nigeria - Shatu Ishaku; Hadiza Mohammed Sani; Hayat Imam Gommaa; Anita Mfuh Y. Lukong; Ishaku Hassan (Asian Journal of Public Health and Nursing, 2026)
Background:  Parental perceived barriers remain a major obstacle to human papillomavirus (HPV) vaccine uptake among adolescents in Nigeria. Community-based nurse-led educational interventions may help address these barriers, but evidence from rural and semi-urban settings is limited. This study aims to assess the effect of a community-based nurse-led educational intervention on parental perceived barriers to HPV vaccine uptake in Kaduna North Senatorial District, Nigeria. Methods: A quasi-experimental pre-test and post-test design with intervention and control groups was conducted among 208 parents of adolescents aged 9–14 years, with 204 completing the study (102 per group). Data were collected using a structured interviewer-administered questionnaire assessing socio-demographic characteristics and perceived barriers. The intervention group received a structured nurse-led educational programme, while the control group received no intervention. Data were analysed using chi-square tests, McNemar’s test, and t-tests, with significance set at p < 0.05. Results: At baseline, there was no significant difference in mean barrier scores between groups (p = 0.652). After the intervention, the study group showed significant reductions in key barriers, including difficulty accessing accurate information, long waiting times, and limited opportunity to discuss concerns (p < 0.001). The mean barrier score decreased significantly in the study group from 5.40 ± 2.03 to 2.07 ± 1.55 (p < 0.001), while no significant change occurred in the control group. Conclusion: The community-based nurse-led educational intervention significantly reduced parental perceived barriers to HPV vaccine uptake, supporting the integration of structured health education into primary healthcare to improve adolescent vaccination outcomes.